2021
DOI: 10.3389/fphar.2021.685011
|View full text |Cite
|
Sign up to set email alerts
|

Post-Translational Modifications of Deubiquitinating Enzymes: Expanding the Ubiquitin Code

Abstract: Post-translational modifications such as ubiquitination play important regulatory roles in several biological processes in eukaryotes. This process could be reversed by deubiquitinating enzymes (DUBs), which remove conjugated ubiquitin molecules from target substrates. Owing to their role as essential enzymes in regulating all ubiquitin-related processes, the abundance, localization, and catalytic activity of DUBs are tightly regulated. Dysregulation of DUBs can cause dramatic physiological consequences and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 245 publications
(326 reference statements)
0
35
0
Order By: Relevance
“…Recently emerging evidence have shown that posttranslational modification of DUBs relates to their abundance, localization, and activity ( Wang and Wang, 2021b ). Dysregulation of these modifications might cause various diseases, such as cancer, inflammatory, and neurodegenerative diseases ( Reyes-Turcu et al, 2009 ; Kessler and Edelmann, 2011 ; Leznicki and Kulathu, 2017 ; Das et al, 2020 ).…”
Section: Regulation Of Usp14 Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently emerging evidence have shown that posttranslational modification of DUBs relates to their abundance, localization, and activity ( Wang and Wang, 2021b ). Dysregulation of these modifications might cause various diseases, such as cancer, inflammatory, and neurodegenerative diseases ( Reyes-Turcu et al, 2009 ; Kessler and Edelmann, 2011 ; Leznicki and Kulathu, 2017 ; Das et al, 2020 ).…”
Section: Regulation Of Usp14 Activitymentioning
confidence: 99%
“…USP14, belonging to the USPs family, is known to be extensively engaged in varying canonical cellular signaling pathways, including nuclear factor kappa B (NF-κB) and Wnt/β catenin signaling pathways ( Harrigan et al, 2018 ; Li et al, 2021 ). Studies have demonstrated that the activity of USP14 is strictly regulated through its association with proteasome and several kinds of postmodifications, such as phosphorylation ( Xu et al, 2015 ; Wang and Wang, 2021b ). Dysregulation of USP14 causes pathological conditions, such as cancer, neurodegenerative disease, autophagy, immune responses, and viral infections ( Wang et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…USP30 plays an important role in various physiological processes and must be tightly regulated to keep its appropriate level and activity in biological events. Nevertheless, understanding of the regulation of USP30 is inadequate, particularly at the post-translational level ( Wang and Wang, 2021 ). Recently, several known regulation ways of USP30 including phosphorylation and ubiquitination were identified, promoting the comprehension and development of appropriate therapeutic strategies.…”
Section: Molecular Characteristics Of Usp30mentioning
confidence: 99%
“…Glycogen synthase kinase 3 beta (GSK3b) interacts with and phosphorylates b-catenin, and the ubiquitin ligase b-TrCP ubiquitinates the b-catenin, leading to degradation by the proteasome (93). Therefore, it is evaluated that b-catenin-370aa binds to GSK3b, which eventually leads to prevent the GSK3B from interacting with full-length b-catenin (92,94).…”
Section: Translation Of Circß-catenin In Hccmentioning
confidence: 99%